Gamma-rays from ultracompact minihaloes: effects on the Earth's atmosphere and links to mass extinction events. Issue 3 (19th April 2021) - Sarkis, M; Beck, G; Thomas, B C
ABSTRACT: Recent studies of the effects on the Earth's atmosphere by astrophysical sources, such as nearby gamma-ray bursts or supernovae, have shown that these events could lead to severe changes in atmospheric composition. Depletion of ozone, the most notable of these changes, is extremely dangerous to living organisms as any decrease in ozone levels leads to an increase in the irradiance of harmful solar radiation at the Earth's surface. In this work, we consider dark matter as an astrophysical source of gamma-rays, by the annihilation and decay of weakly interacting massive particles found within dark compact halo objects known as ultracompact minihaloes (UCMHs). We calculate the fluence of gamma-rays produced in this way and simulate the resulting changes to terrestrial ozone levels using the Goddard Space Flight Center 2D Atmospheric Model. We then calculate the rate at which such events would occur, using estimates for the mass distribution of these haloes within the Milky Way. We find that the ozone depletion from UCMHs can be significant, and even of similar magnitude to the levels which have been linked to the cause of the Late-Ordovician mass extinction event. However, we also find that the rate of such extinction-level events due to UCMHs is markedly lower than for other astrophysical phenomena. This suggests that, while dark compact objects such as UCMHs could have had an impact on the Earth's biosphere, events such as gamma-ray bursts or supernovae seem a more likely source of these effects.